2017
DOI: 10.3390/md15100311
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity, Antioxidant Properties, Phenolic Content and Amino Acid Profiles of Fucus spiralis L. Protein Hydrolysate Fractions

Abstract: Food protein-derived hydrolysates with multi-bioactivities such as antihypertensive and antioxidant properties have recently received special attention since both activities can play significant roles in preventing cardiovascular diseases. This study reports, for the first time, the angiotensin I-converting enzyme (ACE)-inhibition and antioxidant properties of ultrafiltrate fractions (UF) with different molecular weight ranges (<1, 1–3 and ≥3 kDa) obtained from Fucus spiralis protein hydrolysate (FSPH) digeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 75 publications
(110 reference statements)
6
49
1
1
Order By: Relevance
“…Three ultrafiltrate fractions of F. spiralis were obtained after obtaining the protein hydrolysate with the enzymatic digestion by the mixture of two enymes cellulase and bromelain. The results revealed the potent ACE inhibitory activity in fraction 3 (IC 50 : 0.5 mg/ml) than the fraction 1 (IC 50 : 1.85 mg/ml) and fraction 2 (IC 50 : 2 mg/ml) compared to the positive control captopril (IC 50 : 0.163 ng/ml) mainly due to the amino acid composition and phlorotannins released 7 Journal of Diabetes Research during the enzymatic digestion [45]. Cha et al [46] reported the ACE inhibitory activity of some Korean brown seaweeds Sargassum fusiforme, Ishige sinicola, Ecklonia cava, and Sargassum horneri.…”
Section: Inhibitory Activity Of Angiotensin-converting Enzymes (Ace)mentioning
confidence: 97%
See 1 more Smart Citation
“…Three ultrafiltrate fractions of F. spiralis were obtained after obtaining the protein hydrolysate with the enzymatic digestion by the mixture of two enymes cellulase and bromelain. The results revealed the potent ACE inhibitory activity in fraction 3 (IC 50 : 0.5 mg/ml) than the fraction 1 (IC 50 : 1.85 mg/ml) and fraction 2 (IC 50 : 2 mg/ml) compared to the positive control captopril (IC 50 : 0.163 ng/ml) mainly due to the amino acid composition and phlorotannins released 7 Journal of Diabetes Research during the enzymatic digestion [45]. Cha et al [46] reported the ACE inhibitory activity of some Korean brown seaweeds Sargassum fusiforme, Ishige sinicola, Ecklonia cava, and Sargassum horneri.…”
Section: Inhibitory Activity Of Angiotensin-converting Enzymes (Ace)mentioning
confidence: 97%
“…Paiva et al [45] investigated the inhibitory effect of enzymatic protein hydrolysate of brown seaweed Fucus spiralis on ACE. Three ultrafiltrate fractions of F. spiralis were obtained after obtaining the protein hydrolysate with the enzymatic digestion by the mixture of two enymes cellulase and bromelain.…”
Section: Inhibitory Activity Of Angiotensin-converting Enzymes (Ace)mentioning
confidence: 99%
“…Pancreatic lipase is a key enzyme in the process of dietary fat absorption, which is responsible for 50%-70% of the hydrolysis of dietary triglycerides into monoacylglycerides and free fatty acids, finally been absorbed by enterocytes (Sergent, Vanderstraeten, Winand, Beguin, & Schneider, 2012). ACE belongs to the class of zinc metal proteases that catalyzes the conversion of angiotensin I to a potent vasoconstrictor angiotensin II and also promotes the degradation of the vasodilator bradykinin (Paiva, Lima, Neto, & Baptista, 2017). ACE, another enzyme that have an important impact on metabolic syndrome, plays a pivotal role in the regulation of blood pressure (Villiger, Sala, Suter, & Butterweck, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ACE, another enzyme that have an important impact on metabolic syndrome, plays a pivotal role in the regulation of blood pressure (Villiger, Sala, Suter, & Butterweck, 2015). ACE belongs to the class of zinc metal proteases that catalyzes the conversion of angiotensin I to a potent vasoconstrictor angiotensin II and also promotes the degradation of the vasodilator bradykinin (Paiva, Lima, Neto, & Baptista, 2017). Plenty of synthetic drugs, such as captopril, that used in the treatment of hypertension were ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Protective Effects of Captopril in Seizure with ACE inhibitors can diminish the oxidative stress. 25,26 Captopril has been shown to act as a potent free radical scavenger. 27 It has been reported that captopril reduces oxidative stress through attenuating of lipid peroxidation in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%